Australasian Conference on Information Systems 2018 2018
DOI: 10.5130/acis2018.bq
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of e-Tourism Adoption in Developing Countries: A Case Study of Nepal

Abstract: Developing countries lack e-tourism competencies despite attractive destinations to offer. Nepal is one of the developing countries with its natural beauty and diverse cultural heritage that has great tourism potential. This research is aimed at identifying barriers of e-tourism adoption in developing countries, using Nepal as a case study. Based on the Technology, Organization and Environment (TOE) and e-readiness models, and our literature review, we propose ten factors that affect e-tourism adoption. We app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…Several of them are still unaware of the extent and promotional possibilities of social networking platforms for businesses. Lack of awareness becomes an obstacle in the organisation to implement e-tourism, which is consistent with the results of other studies on technology adoption in the tourism industry in Nepal (Lama et al, 2018). Technology awareness also challenges the usage of social media tools for business in Jordan (Al-adaileh et al, 2022).…”
Section: Most Of Us Here Are Already Retired or Having Another Primar...supporting
confidence: 85%
“…Several of them are still unaware of the extent and promotional possibilities of social networking platforms for businesses. Lack of awareness becomes an obstacle in the organisation to implement e-tourism, which is consistent with the results of other studies on technology adoption in the tourism industry in Nepal (Lama et al, 2018). Technology awareness also challenges the usage of social media tools for business in Jordan (Al-adaileh et al, 2022).…”
Section: Most Of Us Here Are Already Retired or Having Another Primar...supporting
confidence: 85%
“…A survey of 198 SMTEs was used to validate the 10 categories in the preliminary etourism adoption model. Reliability and hypothesis tests of these categories have been previously reported [23]. The significance value (p value <0.05) indicates that the factors are significant in the model.…”
Section: Lack Of Trustmentioning
confidence: 94%
“…Each framework and its constructs were examined to assess their relevant for e-tourism adoption study in Nepal. Detailed evaluation of these frameworks relevant to this study has been reported earlier [23].…”
Section: Relevant E-tourism Adoption Modelsmentioning
confidence: 99%
“…Lack of Board Interest Buhalis and Deimezi (2004), Zaidan (2017), Lama et al (2018). Buhalis and Deimezi (2004).…”
Section: Informationmentioning
confidence: 99%